A cinema for the unborn: moving pictures, mental pictures and Electra Sparks's New Thought film theory. Issue 3 (September 2017) - ELLIS, PATRICK
Abstract: In the 1910s, New York suffragette Electra Sparks wrote a series of essays in the Moving Picture News that advocated for cine-therapy treatments for pregnant women. Film was, in her view, the great democratizer of beautiful images, providing high-cultural access to the city's poor. These positive 'mental pictures' were important for her because, she claimed, in order to produce an attractive, healthy child, the mother must be exposed to quality cultural material. Sparks's championing of cinema during its 'second birth' was founded upon the premise of New Thought. This metaphysical Christian doctrine existed alongside the self-help and esoteric publishing domains and testified, above all, to the possibility of the 'mind-cure' of the body through the positive application of 'mental pictures'. Physiologically, their method began best in the womb, where the thoughts of the mother were of utmost importance: the eventual difference between birthing an Elephant Man or an Adonis. This positive maternal impression was commonplace in New Thought literature; it was Sparks's innovation to apply it to cinema. Investigating Sparks's film theory, practice and programming reveals her to be a harbinger of the abiding analogy between mind and motion picture that occupies film theorists to this day.